Race, science, and the nation reconstructing the ancient past in Britain, France and Germany - Manias, Chris (Routledge studies in cultural history, 2013)
1. Unveiling the ancestry of peoples : tradition, language and ethnology, 1800-1860 -- 2. Unearthing our forefathers : the growth of provincial archaeology, 1830-1860 -- 3. The limits of history : defining nations, races and peoples, 1820-1850 -- 4. Building the science of man : national anthropology and the ancient past, 1850-1870 -- 5. Locating the peoples of prehistory : geology, archaeology and anthropology, 1840-1870 -- 6. The fracturing of common origins : the nationalization of the anthropological past, 1871-1900 -- 7. Tension and diffusion : the racial and cultural sciences, 1890-1914.